Samotność metafizyczna - Kopania, Jerzy (Zeszyty Naukowe Centrum Badań im. Edyty Stein, 2014)
In psychological terms, loneliness is usually understood as a state subjectively perceived by an individual as a deficiency of desired relationships with other people. However, this kind of loneliness must be grounded in the ontic nature of reality. The basic type of loneliness experienced by the human being is metaphysical loneliness. It involves the inability to answer the basic questions of an existential character which an individual asks about nature, fate, other people and God. This kind of loneliness is irremovablebecause it stems from the nature of reality, and, as such, it is an important determinant of human existence.